2016
DOI: 10.1038/srep24576
|View full text |Cite
|
Sign up to set email alerts
|

SPECT-OPT multimodal imaging enables accurate evaluation of radiotracers for β-cell mass assessments

Abstract: Single Photon Emission Computed Tomography (SPECT) has become a promising experimental approach to monitor changes in β-cell mass (BCM) during diabetes progression. SPECT imaging of pancreatic islets is most commonly cross-validated by stereological analysis of histological pancreatic sections after insulin staining. Typically, stereological methods do not accurately determine the total β-cell volume, which is inconvenient when correlating total pancreatic tracer uptake with BCM. Alternative methods are theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Previous work demonstrated the mechanism and the specificity of tracers targeting GLP-1R for insulin-positive β-cells in the pancreas 13, 28, 29. Several studies showed that the specific accumulation of radiolabeled exendin-derivatives enabled the detection of islet β-cells clusters in control and diabetic murine models even in viable cells with insulin content below the detection limits of current immunohistochemical methods 13, 30, 31. Here, we demonstrated that the uptake of our PET tracer by the pancreatic insulinomas is colocalized with insulin-secreting cells expressing GLP-1R.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated the mechanism and the specificity of tracers targeting GLP-1R for insulin-positive β-cells in the pancreas 13, 28, 29. Several studies showed that the specific accumulation of radiolabeled exendin-derivatives enabled the detection of islet β-cells clusters in control and diabetic murine models even in viable cells with insulin content below the detection limits of current immunohistochemical methods 13, 30, 31. Here, we demonstrated that the uptake of our PET tracer by the pancreatic insulinomas is colocalized with insulin-secreting cells expressing GLP-1R.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups, including ours, are developing radiolabeled exendin derivatives 58,16,17 . However, most of the previous reports have used SPECT scan not with living mice but with resected pancreata 18,19 , and longitudinal observation of BCM has not been achieved. In order to enable longitudinal observation, we established an analytical method using SPECT imaging of living mice to quantify pancreatic uptake of [ 111 In]Ex4 9 ; we reported a correlation between pancreatic uptake and BCM and also a longitudinal decrease in BCM in NOD mice, an animal model of type 1 diabetes 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the possibility of calculating absolute islet numbers and even their individual volumes in pancreatic specimens labeled with islet-specific markers (see e.g., [72,73]), this technique may be considered as a gold standard against other imaging assessments. Indeed, we have shown that 111 Inexendin-3 SPECT imaging and OPT linearly correlates and both techniques are more reliable than histological assessment of β cell mass [74]. A recent standardized approach has been postulated to define criteria that β cell traces should fulfill [45].…”
Section: Box 3 Preclinical Approaches For β Cell Evaluation In Diabetesmentioning
confidence: 97%